PEMBERIAN AIR REBUSAN DAUN SIRIH MERAH (Piper crocatum Ruiz &Pav) TERHADAP KADAR GLUKOSA DAN KOLESTEROL DARAH MENCIT PUTIH JANTAN - Shinta, Dewi Yudiana; Sudyanto, Sudyanto (IAIN Batusangkar, 2016)
This study aims to find of the effect of the water decoction of red betel leaf (Piper crocatum Ruiz & Pav) on blood glucose levels and cholesterol male white mice. The method used in this study deskripstif exploration using betel leaf stew and given to a white male mice are sonde at a dose of 0.13 ml / 20gBB, 0.13 to 0.39 ml / 20gBB 0.13 and 0.26 ml / 20gBB during seven days and examined glucose and cholesterol levels of the mice. Research results show that the water decoction of red betel leaf (Piper crocatum Ruiz & Pav) can lower blood glucose levels of male white mice were significantly (p <0.05) by ANOVA statistical analysis.